The role of investment in social reproduction: theoretical aspect - V. Rokotyanskaya, Violetta (2020)
The process of social reproduction is a necessary basis for the existence of human society and, at the same time, it is understood as the system of production, distribution, exchange and consumption. Investments, first of all, determine the first link of this system (production), and serve as a material basis for development. Despite this obviousness, discussion about the modern role of investment in the development of the economy in general, and the social sphere in particular, has recently become relevant in the scientific environment. Therefore, this article investigates the content of investments in the context of their functional role in expanded reproduction.